2010
DOI: 10.1510/icvts.2009.224212
|View full text |Cite
|
Sign up to set email alerts
|

Clinical mid-term results after tricuspid valve replacement☆

Abstract: Tricuspid valve replacement (TVR) is associated with high mortality and morbidity. Frequently, TVR is performed in critically ill patients with high frequency of re-intervention. We analyzed our experience in TVR focusing on predicting risk factors, mid-term survival and quality of life assessed with a Short-Form 36 Health Survey (SF-36) questionnaire. Between January 1992 and May 2007, 81 consecutive patients underwent TVR (54 re-interventions, 66.7%; 46 procedures, associated with a left-sided operation, 56.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
9
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 13 publications
5
9
1
Order By: Relevance
“…In our cohort, the operative mortality was 19.4%, similar to other previously published studies, which shows mortality rates between 5 and 25%, with a progressive decline in recent years . Our mortality results are in accordance with those reported in the literature, which are usually in the range of 25‐40%, with the only exception of Park et al who reported a relatively low mid‐term mortality. Rodríguez‐Capitán et al reported a perioperative mortality of 18.5% for tricuspid valve surgery, with a mortality of 29.9% at 41 months follow‐up.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our cohort, the operative mortality was 19.4%, similar to other previously published studies, which shows mortality rates between 5 and 25%, with a progressive decline in recent years . Our mortality results are in accordance with those reported in the literature, which are usually in the range of 25‐40%, with the only exception of Park et al who reported a relatively low mid‐term mortality. Rodríguez‐Capitán et al reported a perioperative mortality of 18.5% for tricuspid valve surgery, with a mortality of 29.9% at 41 months follow‐up.…”
Section: Discussionsupporting
confidence: 91%
“…Previous publications addressing the impact of TVR have not been specifically focused on mechanical valves. In these studies, operative mortality has been reported in the range of 5‐25%, whereas long‐term mortality is usually in the range of 25‐40% . In the present study, we analyzed mortality and morbidity of patients who underwent mechanical TVR.…”
Section: Introductionmentioning
confidence: 96%
“…Additionally, patients who develop progressive TR late after left-sided valve surgery represent a particular challenge (14). In this subgroup, despite medical management, surgical correction is associated with a higher risk of morbidity and mortality as a result of the presence of variable degrees of RV dysfunction, pulmonary vascular disease, and right heart failure.…”
mentioning
confidence: 99%
“…A prospective randomized study of 159 patients conducted by Rivera et al comparing De Vega suture to ring anuloplasty demonstrated higher recurrence of moderate and sever TR in the De Vega group. 25,26 Similarly, a study of 790 patients by McCarthy et al reported an earlier recurrence and progressive increase of moderate and severe TR after De Vega repair compared with ring annuloplasty. 26,27 The retrospective nature of the study and the single centre design are the major limitations…”
Section: Discussionmentioning
confidence: 96%